Wprowadzenie: teologia jako krytyka - Mikołaj Ratajczak; Rafał Zawisza (Praktyka Teoretyczna, 2015)
This is an introduction to the issue of “Theoretical Practice” (“Praktyka Teoretyczna”), entitled “Economic Theologies” (no. 3, 2015), edited by Mikołaj Ratajczak and Rafał Zawisza. It contains contextual explanation of the theoretical field projected by the Italian philosopher Giorgio Agamben, namely a critique of the economic theology elaborated on the basis of early Christian theological debates concerning the concept of divine “oikonomia”. The introduction also includes short summaries of the articles, translations and reviews collected in the issue.